Issues of management and monitoring by laboratory methods in respiratory medicine: editorial introduction - Nwose, Ezekiel Uba (International Journal of Research in Medical Sciences, 2017)
There is a gap in knowledge, attitude and practice (KAP), as well as between findings of experimental versus clinical observational studies in respiratory diseases. Hence, research is on-going especially in disease management and monitoring by laboratory methods. A cursory review or passive discussion of laboratory services will reveal that the service and research provisions of Pathology are challenging in view of fiscal constraints and other competing forces.